ANALISA EFEKTIFITAS METODE FORWARD CHAINING DAN BACKWARD CHAINING PADA SISTEM PAKAR - Akil, Ibnu (LPPM Universitas Nusa Mandiri, 2017)
The use of forward-chaining and backward-chaining in an expert system is something usual. Where forward-chaining is a data-driven algorithm, while backward-chaining is goal-driven. Both methods are usually used for reasoning. Here, the writer will analyze effectively both method in their using for an expert system.